HUBUNGAN KREATIVITAS TERHADAP HASIL BELAJAR DENGAN MODEL PJBL PADA MATERI BIOTEKNOLOGI KELAS IX - Kusmiati, Evy; Ningsih, Kurnia; Ariyanti, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the creativity and learning outcomes and find out whether there is a positive relationship between the creativity with students the learning outcomes  who are taught with the project based learning (PjBL) model in class IX biotechnology material SMPN 1 Pontianak. This research is correlation research. The research sample is class IX G taken using purposive sampling technique. The instrument used was a test of creativity and a test of learning outcomes. The hypothesis was tested using Pearson moment product correlation analysis. The results showed (1) IX grade students of SMPN 1 Pontianak had moderate creativity with a percentage of 67%; (2) grade IX students of SMPN 1 Pontianak meet the KKM with a percentage of 33%; (3) there is a positive relationship between the creativity taught with the PjBL model and student learning outcomes in biotechnology material class IX SMPN 1 Pontianak. The relationship is shown through the correlation coefficient of rcount of 0.396 greater than rtable of 0.344. The coefficient of determination obtained by 15.68% indicates variations in learning outcomes can be explained through the creativity of the rest is influenced by factors not examined. The correlation coefficient obtained positive sign (+) shows the relationship between creativity in the direction of student learning outcomes. Creativity is high thinking so the learning outcomes are also high.  Keywords: Creativity, learning outcomes, PjBL